Comparação entre duas formulações do método dos elementos de contorno: a que faz integração direta e a que usa solução fundamental dependente da frequência em problemas bidimensionais governados pela equação de Helmholtz - Pereira, Pedro Vinicius Moreira (2016)
The thermochemical conversion processes are ways to convert solids into more convenient energy carriers (charcoal), or turn them into liquid and gaseous fuels, or also heat or other diverse products. Many studies have been conducted aimming to make the thermochemical processes more efficient and economically viable.The application of Computational Fluid Dynamics (CFD) models helps to optimize the design and operation of the thermochemical reactors, such as fixed bed reactors. The free CFD softwares offer a cost-effective tool for these studies. One such software that is gaining prominence is OpenFOAM. An solver for OpenFOAM called biomassGasificationFoam was recently published for the simulation of biomass gasification in fixed bed. In this work, it was done an evaluation of the solver biomassGasificationFoam and the auxiliary libraries that accompany it, in order to generalize their applicability in various solids thermochemical conversion processes in fixed bed. Its models for heat and mass transport in a reactive porous medium were verified and validated with proposed tests, analytical equations and experiments. Some code details were changed and improvements were implemented. It was identified an overestimation of the diffusion process of the gaseous species caused by a hypothesis adopted in these species conservation equation. The kinetic model showed to be suitable for solid thermal decomposition processes where the reaction order is unitary. However, this model was not so suitable for solid homogeneous reactions where the reaction order is different from one and for heterogeneous reactions. In overall, the biomassGasificationFoam presents an interesting potential, an useful tool for the simulation of many solids thermochemical conversion processes in fixed bed. Finally, informations were provided about the software OpenFOAM, and, especially, about the biomassGasificationFoam, in order to serve as documentation to help future users interested in its use